2015
DOI: 10.1007/s40263-015-0255-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Opioid-Induced Hyperalgesia in Clinical Treatment: Neurobiological Considerations

Abstract: Opioid analgesics have become a cornerstone in the treatment of moderate to severe pain, resulting in a steady rise of opioid prescriptions. Subsequently, there has been a striking increase in the number of opioid-dependent individuals, opioid-related overdoses, and fatalities. Clinical use of opioids is further complicated by an increasingly deleterious profile of side effects beyond addiction, including tolerance and opioid-induced hyperalgesia (OIH), where OIH is defined as an increased sensitivity to alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 263 publications
(382 reference statements)
1
57
0
Order By: Relevance
“…6,39,60,68,73,80,112,133,134 Along with opioid, neurokinin 1, and toll-like receptor 4 antagonists, NSAIDS and gabapentinoids have been found to reduce neuroinflammation and mitigate OIH and/or WIH in some 1,5,14,18,34,45,46,61,70,83,85,94,100,121,127,135,137 but not all 50 circumstances. In our study, a subset of participants named NSAIDs most frequently and gabapentinoids third for relieving WISP, supporting a possible neuroinflammatory component.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,39,60,68,73,80,112,133,134 Along with opioid, neurokinin 1, and toll-like receptor 4 antagonists, NSAIDS and gabapentinoids have been found to reduce neuroinflammation and mitigate OIH and/or WIH in some 1,5,14,18,34,45,46,61,70,83,85,94,100,121,127,135,137 but not all 50 circumstances. In our study, a subset of participants named NSAIDs most frequently and gabapentinoids third for relieving WISP, supporting a possible neuroinflammatory component.…”
Section: Discussionmentioning
confidence: 99%
“…Although these may be coincidental, there is evidence that these or related substances may mitigate OIH, WIH, or other forms of pain through modulation of one of the above mechanisms, some of which are also involved with gabapentinoids. 6,74,94,111,113,116 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That this data did not yield significant results was perhaps unsurprising, given the recent decrease in opioid use due to dependence [18], overdose [19], and opioid-induced hyperalgesia [20]. A 2007 study examining ONA's effect on occipital neuralgia showed opioid use in all six of its patients [15]; in contrast, only 21 of 63 patients in this study had received opioid prescriptions, 19 of which were PRN dosages for short-acting relief.…”
Section: Discussionmentioning
confidence: 68%